Toll-Like Receptor 4 (TLR4)/Opioid Receptor Pathway Crosstalk and Impact on Opioid Analgesia, Immune Function, and Gastrointestinal Motility - Zhang, Peng; Yang, Meirong; Chen, Chunhua; Liu, Liu; Wei, Xinchuan; Zeng, Si (Frontiers in Immunology, 2020)
TLR4 recognizes exogenous pathogen-associated molecular patterns (PAMPs) and endogenous danger-associated molecular patterns (DAMPs) and initiates the innate immune response. Opioid receptors (µ, δ, and κ) activate inhibitory G-proteins and relieve pain. The following TLR4/opioid receptor pathway crosstalk has been identified: (a) Opioid receptor agonists nonstereoselectively activate TLR4 signaling pathway in CNS, in the absence of LPS. (b) Opioid receptor agonists inhibit LPS-induced TLR4 signaling pathway in peripheral immune cells. Opioids operate as proinflammatory cytokines resulting in neuroinflammation in CNS, but they mediate immunosuppressive effects in peripheral immune system. It is apparent that TLR4/opioid receptor pathway crosstalk varies dependent on cell type and activating stimulus. (c) Both TLR4 and opioid receptor pathway activate mitogen-activated protein kinase (MAPK) pathway. This crosstalk locates in the downstream of TLR4 and opioid receptor signaling pathway. Furthermore, it is indicated that classic opioid receptor also can produce proinflammatory effects in CNS via MAPK signaling and induce neuroinflammation. (d) Opioid receptor agonists induce production of high mobility group box 1 (HMGB1), an endogenous TLR4 agonists, supporting an intercellular interaction (neuron-to-glia or glia-to-neuron interaction). This review also summarizes the potential effect of TLR4/opioid receptor pathway crosstalk on opioid analgesia, immune function and gastrointestinal motility. Opioids nonstereoselective activation of TLR4 pathway, together with release of proinflammatory cytokines such as IL-1 in glia, provide a common initiating trigger to the central immune signaling response and modify opioid pharmacodynamics. DAMPs HMGB1 correlates with the development of neuropathic pain. A positive feedback loop, wherein an initial amplified release of IL-1β and exacerbated release of DAMPs that signal back at TLR4 and purinergic receptor P2X7R, was introduced to explain morphine-induced persistent sensitization. Opioid receptor (µ, δ, and κ) agonists involved in many aspects of immunosuppression. The intracellular TLR4/opioid receptor signaling pathway crosstalk induce the formation of β-arrestin2/TRAF6 complex which contribute to morphine inhibition of LPS-induced secretion of TNF-α in mast cells. The possible molecular mechanism is that TLR4 pathway initially triggers the formation of -arrestin-2/TRAF6 complex which is amplified by opioid receptor pathway, suggesting -arrestin-2 act as a functional component of TLR4 pathway.